The One that Wasn’t: Child and Youth Labour in the Post-Stalin Era in the Soviet Union - Studenna-Skrukwa , Marta (Studia Historiae Oeconomicae, 2023)
This paper examines the phenomenon of child and youth labour in the post-Stalin era in the Soviet Union. The starting point for the consideration constitutes the analysis of the law adopted by the Supreme Soviet of the USSR in 1958 titled “On the strengthening of the link between school and life and the further development of people’s education in the USSR”. This law placed great emphasis on combining education with practice and involving pupils from the earliest grades in various forms of both productive and socially useful labour. Subsequently, four categories of labour to which children and young people in the USSR were systemically forced has been distinguished. These included: occasional labours, work and leisure camps, so-called subbotniki and little communal works, as well as compulsory recycling. The paper thoroughly depicts all of them in the light of memoir material.